A phase II randomized trial comparing standard and low dose rituximab combined with alemtuzumab as initial treatment of progressive chronic lymphocytic leukemia in older patients: a trial of the ECOG‐ACRIN cancer research group (E1908). Issue 3 (9th February 2016) - Zent, Clive S.; Victoria Wang, Xin; Ketterling, Rhett P.; Hanson, Curtis A.; Libby, Edward N.; Barrientos, Jacqueline C.; Call, Timothy G.; Chang, Julie E.; Liu, Jane J.; Calvo, Alejandro R.; Lazarus, Hillard M.; Rowe, Jacob M.; et al.
Abstract : Chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL) patients requiring initial therapy are often older and frailer and unsuitable candidates for standard chemoimmunotherapy regimens. Shorter duration combination monoclonal antibody (mAb) therapy using alemtuzumab and rituximab has been shown to be effective and tolerable treatment for CLL. Standard dose anti‐CD20 mAb therapy causes loss of CD20 expression by surviving CLL cells, which can be minimized by decreasing the mAb dose. We report a randomized phase II clinical trial enrolling older (≥ 65 years) patients (median age 76 years, n = 31) with treatment naïve progressive CLL. Patients received 8‐12 weeks of standard subcutaneous alemtuzumab with either intravenous standard (375 mg/m 2 weekly)( n = 16) or low dose (20 mg/m 2 3x week)( n = 15) rituximab. This study was closed before full accrual because the manufacturer withdrew alemtuzumab for treatment of CLL. The overall response rate was 90% with an 45% complete response rate, median progression‐free survival of 17.9 months and no significant differences in outcome between the low and standard dose rituximab arms. The major toxicities were cytopenia and infection with one treatment fatality caused by progressive multifocal leukoencephalopathy but no other opportunistic infections. Combination mAb therapy was effective and tolerable treatment for older and frailer patients with progressive CLL, achieving a high rate of complete remissions. These data support the role of mAb in therapy for less fit CLL patients and the further study of low dose higher frequency anti‐CD20 mAb therapy as a potentially more effective use of anti‐CD20 mAb in the treatment of CLL. Am. J. Hematol. 91:308–312, 2016. © 2015 Wiley Periodicals, Inc.